PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP KEAKTIFAN SISWA PADA PEMBELAJARAN IPS KELAS IV SDN CIPAYUNG DEPOK - Raudhiyatuzzahra Fajriyati; Ali Sya'ban, Muhammad Balya (Prosiding Seminar Nasional Berseri, 2020)
The Effect of the Use of Course Review Horay Learning Models on Student Activity in Social Studies Learning of Class IV SDN Cipayung Depok". Jakarta: Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, University Muhammadiyah Prof. DR. HAMKA, 2019. This research aims to determine whether or not there is an effect of the use of Course Review Horay learning models on student activity in social studies learning of class IV SDN Cipayung Depok of the 2019-2020 academic year. The research method used is a quasi experimental quantitative research method with Posttest Only Design research design. The sample used is Saturated Sample. In the validity test using the Product Moment formula as many as 30 items closed statement questionnaire instruments with the results of 20 items valid instruments, while the reliability test using the Alpha Cronbach and the instrument data is reliable. Furthermore, the data were analyzed by the requirements test by the Normality test using the Liliefors test, it was found that the two data were normally distributed. While the homogeneity test using Fisher's test and found that this research has variance data for homogeneous distributed groups. In the hypothesis test, the t-test was used. H0 is rejected and H1 is accepted, which states that there is an effect of the Course Review Horay learning model on student activity in social studies learning at class IV SDN Cipayung Depok. The results of this research conclude that there is an effect of the Course Review Horay learning model on student activity in social studies learning in class IV